Determinants of relationship quality: the role of relationship between parents, previous romantic experiences, attachment and self-disclosure of both partners - Jelić, Margareta (Array, 2010)
The primary aim of this study was to determine the role of some situational and personal characteristics on the perception of the relationship quality. Perception of relationship between parents and one’s previous romantic experiences were included as situational variables, whereas attachment and self-disclosure to romantic partner were included as personal variables. Another aim was to determine the role of partner’s characteristics (above the effect of participants’ own characteristics) in explaining the perception of the relationship quality. Sample consisted of 161 romantic couples aged between 18 and 40 years. The questionnaire consisted of the shortened version of Experience in Close Relations Inventory (Kamenov & Jelic, 2003), The Revised Scale of Self-disclosure (Wheelees & Grotz, 1976), Quality of Marriage Index (Norton, 1983) as well as information on previous romantic relationships (number, duration of the longest relationship and satisfaction with past romantic experiences), perception of relationship between parents (positive and negative interactions between parents, perceived parental satisfaction with their marriage and perceived quality of parental relationship) and demographic data. Regression analyses were conducted separately for each gender. Past romantic experiences proved to be the most important predictor of current relationship quality for both genders, whereas gender differences were found for all other included variables. Further more results have shown that one’s own personal and situational characteristics are more important for the evaluation of the relationship quality than characteristics of the partner. However, partner’s experiences and characteristics have certain effect on the perception of the relationship quality.